rBMSC/Cav-1F92A Mediates Oxidative Stress in PAH Rat by Regulating SelW/14-3-3η and CA1/Kininogen Signal Transduction - Wan-cheng Yu; Hai-ying Chen; Hong-li Yang; Peng Xia; Cheng-wei Zou; Tong-wen Sun; Le-xin Wang (Stem Cells International)
Background/Objectives. Carbonic anhydrase 1 (CA1)/kininogen and selenoprotein W (SelW)/14-3-3η signal transduction orchestrate oxidative stress, which can also be regulated by nitric oxide (NO). The mutated caveolin-1 (Cav-1F92A) gene may enhance NO production. This study explored the effect of Cav-1F92A-modified rat bone marrow mesenchymal stem cells (rBMSC/Cav-1F92A) on oxidative stress regulation through CA1/kininogen and SelW/14-3-3η signal transduction in a rat model of monocrotaline- (MCT-) induced pulmonary arterial hypertension (PAH). Method. PAH was induced in rats through the subcutaneous injection of MCT. Next, rBMSC/Vector (negative control), rBMSC/Cav-1, rBMSC/Cav-1F92A, or rBMSC/Cav-1F92A+L-NAME were administered to the rats. Changes in pulmonary hemodynamic and vascular morphometry and oxidative stress levels were evaluated. CA1/kininogen and SelW/14-3-3η signal transduction, endothelial nitric oxide synthase (eNOS) dimerization, and eNOS/NO/sGC/cGMP pathway changes were determined through real-time polymerase chain reaction, Western blot, or immunohistochemical analyses. Results. In MCT-induced PAH rats, rBMSC/Cav-1F92A treatment reduced right ventricular systolic pressure, vascular stenosis, and oxidative stress; downregulated CA1/kininogen signal transduction; upregulated SelW/14-3-3η signal transduction; and reactivated the NO pathway. Conclusions. In a rat model of MCT-induced PAH, rBMSC/Cav-1F92A reduced oxidative stress by regulating CA1/kininogen and SelW/14-3-3η signal transduction.